Control of the black rot fungus, Fusarium sp; by different densities of the fungus Trichoderma sp. - Aquiloña, Maytell (Iloilo City UPHSI, 2001)
Carrot, which is rich in vitamin A, is very essential to our diet and is one of the economically important crop. Since it is a root crop, it is prone to diseases caused by fungi in the soil. Fusarium sp. is one of the fungi that can be found in soil. Farmers in Benguet claim that a "new" disease in carrots had affected their yield. This black rot disease was found to be caused by Fusarium sp. This research aimed to find a solution to this problem with a biocontrol agent, Trichoderma sp., which is also found in soil. The researchers would like to determine the potential of Trichoderma sp. and its optimum density to control and suppress the growth of the pathogen. Fusarium sp. was isolated from carrots and was inoculated in its host together with Trichoderma sp. and its optimum density to control and suppress the growth of the pathogen. Fusarium sp. was isolated from carrots and was inoculated in its host together with Trichoderma sp., both in wounded and unwounded carrots. It was observed in the replicates of unwounded carrots that Trichoderma sp. was able to control the growth of and development of the pathogen in its heaviest density (2 x 10^9 conidia/ml).
Research II : Research Manuscripts
Keywords: Fungus - Fusarium sp; Trichoderma sp